Hydroperiod Influences Tadpole Growth and Development in the Endangered Littlejohn's Tree Frog (Litoria littlejohni) - Nadine Nolan; Matt Hayward; Alex Callen; Kaya Klop‐Toker (Ecology and Evolution)
ABSTRACT Amphibians are among the most threatened vertebrate taxa globally. Their global decline necessitates effective conservation actions to bolster populations across both the larval and adult stages. Constructing man‐made ponds is one action proven to enhance reproduction in pond‐breeding amphibians. However, to achieve successful conservation outcomes, extensive knowledge about the ecology and behavior of the target species is required. In this study, we investigated how different hydroperiod regimes impacted the growth and development of Litoria littlejohni tadpoles. Over a 28‐week period, tadpoles were exposed to three hydroperiod treatments: constant high, declining, and constant low water levels. Weekly measurements of snout‐vent length, body mass, and Gosner stage were taken to assess treatment‐related changes. To determine whether different treatments affected locomotor performance, jump tests were conducted 3 weeks post‐metamorphosis. Individuals exhibited limited developmental plasticity in response to declining water, with a mean time to metamorphosis of 85.1 days ± 12.1. Comparatively, when L. littlejohni tadpoles were exposed to low water volumes, they were able to speed up development and reduce time to metamorphosis, with a mean time of 63.7 days ± 10.3. The speeding up of development had an apparent consequence for L. littlejohni. We found support for trade‐offs between rapid development and reduced morphometric measurements postmetamorphosis which resulted in reduced locomotive ability. Individuals from constant low water treatments exhibited an average total jumping distance of 171 cm ± 13.6 over 10 consecutive jumps, compared with 236 cm ± 17.3 in constant high and 210 cm ± 14.8 in declining treatments. Rapid larval development aids tadpoles in escaping suboptimal aquatic conditions, but its effects on locomotion may impact foraging efficiency and predator escape ability. Understanding developmental plasticity in threatened amphibians, especially in response to hydroperiod variations, is crucial for conservation programs, particularly under future climate change scenarios predicting increased drought and reduced hydroperiods in aquatic environments.